miRNA-486 and miRNA-499 in human plasma evaluate the clinical stages of lung cancer and play a role as a tumor suppressor in lung tumorigeneisis not pathogenesis (Bangladesh Journal of Pharmacology, 2016)
It was aimed to explore the expression level of miRNA-486 and miRNA-499 in the plasma of lung cancer patients and analysis their differences in expre-ssion. The expression level of both miRNA-486 and miRNA-499 in the plasma of non-small cell lung cancer (NSCLC) and small cell lung cancer (SCLC) were lower than that of the control group (p